A138 LONG-TERM OUTCOMES AFTER PRIMARY BOWEL RESECTION IN PEDIATRIC-ONSET CROHN'S DISEASE. (1st March 2018) - Rinawi, F; Shamir, R; Assa, A
Abstract: Background: There is limited evidence on the long-term outcome of intestinal resection in pediatric-onset Crohn's disease (POCD) with no established predictors of adverse outcomes. Aims: We aimed to investigate clinical outcomes and predictors for adverse outcome following intestinal resection in POCD. Methods: The medical records of patients with POCD who underwent at least one intestinal resection between 1990 and 2014 were reviewed retrospectively. Main outcome measures included time to first flare, hospitalization, second intestinal resection and to non-prophylactic biologic therapy. Results: Overall, 121 patients were included. Median follow-up was 6 years (range 1–23.6). One hundred and seven (88%) patients experienced at least one post-surgical exacerbation, 52 (43%) were hospitalized and 17 (14%) underwent second intestinal resection. Of 91 patients who underwent surgery after the year 2000, 37 (41%) were treated with anti-tumor necrosis factor α (anti-TNFα) (not prophylactic) following intestinal resection. Time to hospitalization and to second intestinal resection were shorter among patients with extra-intestinal manifestations (EIMs) (HR 2.7, P=0.006 and HR=3.1, P= 0.03, respectively). Time to initiation of biologic treatment was shorter in patients with granulomas (HR 2.1, P=0.038), while being naïve to anti-TNFα treatment prior to surgery was a protective factor for biologic treatment following surgery (HR 0.3, P=0.005). Undergoing intestinal resection beyond the year 2000 was associated with shorter time to first flare (HR 1.9, P=0.019) and hospitalization (HR 2.6, P=0.028). Conclusions: Long term risk for flares, hospitalization or biologic treatment is significant in POCD following bowel resection. EIMs increase the risk for hospitalization and second intestinal resection Funding Agencies: None